2016
DOI: 10.1371/journal.pone.0154949
|View full text |Cite
|
Sign up to set email alerts
|

Subsets of Visceral Adipose Tissue Nuclei with Distinct Levels of 5-Hydroxymethylcytosine

Abstract: The reprogramming of cellular memory in specific cell types, and in visceral adipocytes in particular, appears to be a fundamental aspect of obesity and its related negative health outcomes. We explored the hypothesis that adipose tissue contains epigenetically distinct subpopulations of adipocytes that are differentially potentiated to record cellular memories of their environment. Adipocytes are large, fragile, and technically difficult to efficiently isolate and fractionate. We developed fluorescence nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 113 publications
(149 reference statements)
0
8
0
Order By: Relevance
“…Similarly, reduced DNA methylation is observed during adipogenesis at the promoters of other adipocyte genes (e.g., Lep [ 30 ], Slc2a4 [GLUT4] [ 30 ], and Peln [ 27 ]). Intriguingly, recent global profiling studies have demonstrated that 5hmC (a cytosine that is an intermediate product of DNA demethylation) colocalizes with PPARγ at enhancers in 3T3-L1 adipocytes ( 31 ), and PPARγ-positive nuclei sorted from visceral adipose tissue from healthy humans are strongly coenriched with 5hmC ( 32 ). Given that the TET proteins, especially TET1 and TET2, are necessary for adipose conversion ( 33 ) and that PPARγ physically interacts with them ( 27 , 34 ) indicate that PPARγ is influencing the methylation pattern.…”
Section: Dna Methylation In Adipogenesismentioning
confidence: 99%
“…Similarly, reduced DNA methylation is observed during adipogenesis at the promoters of other adipocyte genes (e.g., Lep [ 30 ], Slc2a4 [GLUT4] [ 30 ], and Peln [ 27 ]). Intriguingly, recent global profiling studies have demonstrated that 5hmC (a cytosine that is an intermediate product of DNA demethylation) colocalizes with PPARγ at enhancers in 3T3-L1 adipocytes ( 31 ), and PPARγ-positive nuclei sorted from visceral adipose tissue from healthy humans are strongly coenriched with 5hmC ( 32 ). Given that the TET proteins, especially TET1 and TET2, are necessary for adipose conversion ( 33 ) and that PPARγ physically interacts with them ( 27 , 34 ) indicate that PPARγ is influencing the methylation pattern.…”
Section: Dna Methylation In Adipogenesismentioning
confidence: 99%
“…A recent large-scale functional association analysis from GWAS data identified a genetic variant within TET2 (rs9884482) that associates with fasting insulin level, suggesting an impact on insulin resistance [19]. Furthermore, recent global profiling studies have demonstrated that 5hmC colocalizes with PPARγ binding at enhancers in 3T3-L1 adipocytes [20], and PPARγ-positive nuclei sorted from visceral adipose tissue from healthy humans is strongly co-enriched with 5hmC [21]. Together, these studies suggest the presence of functional and physical interactions between TET proteins and PPARγ.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, 5hmC levels in VAT have been positively related to age and negatively associated with LDL cholesterol in humans 91 . In VAT, it has been shown that 5hmC levels were higher in the adipocyte (defined by PPARγ positive cells) versus the non‐adipocyte fraction and that the differences in 5hmC levels could have a high impact on transcription 92 . in vitro studies have also demonstrated a possible role of 5hmC in adipocyte differentiation.…”
Section: Role Of Lifestyle and Nutritional Conditions In The Epigenetmentioning
confidence: 99%